Antigone rising : the subversive power of the ancient myths - Morales, Helen (Bold Type Books, 2020)
"The picture of classical antiquity most of us learned in school is framed in certain ways -- glossing over misogyny while omitting the seeds of feminist resistance. Many of today's harmful practices, like school dress codes, exploitation of the environment, and rape culture, have their roots in the ancient world. But in Antigone Rising, classicist Helen Morales reminds us that the myths have subversive power because they are told -- and read -- in different ways. Through these stories, whether it's Antigone's courageous stand against tyranny or the indestructible Caeneus, who inspires trans and gender queer people today, Morales uncovers hidden truths about solidarity, empowerment, and catharsis. Antigone Rising offers a fresh understanding of the stories we take for granted, showing how we can reclaim them to challenge the status quo, spark resistance, and rail against unjust regimes."--Amazon.com.